چوار مەزهەبەكەی سوننە لە ناوچە كوردنشینەكان سەدەی چوارەمی كۆچی تا كۆتایی سەردەمی عەباسی - اسماعيل, پ.د.صلاح كانبى; محمد, ياسين طه (Sulaimani Journal for Humanities, 2023)
This study focuses on the emergence of the four schools of jurisprudence (Hanafi, Maliki, Shafi'i, Hanbali) in general, as well as the impact of these doctrines on the Kurdish areas under the Abbasid state during the During the period between the fourth century AH / tenth century AD to the end of the Abbasid state (656 AH / 1258 AD). The study relies mainly on the historical and civilizational research method, and uses analysis to bridge the historical gaps in the light of the general context. The research seeks to answer a number of questions, such as: Does the Kurdish majority adopt the Shafi'i school of thought? Efforts of sects to reach the Kurdish areas and the reasons why some of them stumbled? And know the reasons for the spread of some schools of jurisprudence among the Kurds without others? With an attempt to understand the doctrinal map that prevailed in Kurdistan during the Islamic Middle Ages.
Keywords: وشە كلیلەكان چوار مەزهەبەكە ناوچە كوردنشینەكان حەنەفی شافیعی مالیكی حەنبەلی